Enmerkar and the Lord of Aratta - Cohen, Sol
A Dissertation in Oriental Studies Presented to the Faculty of the Graduate School of Arts and Sciences of the University of Pennsylvania in Partial Fulfillment of the Requirements for the Degree of Doctor of Philosophy; University Microfilms 73-24,127.